Re-evaluation of the morphology and distribution of the newly described species Tirpitzia meiguensis (Linaceae) - Chen, Hong; Luo, Qiang; Yuan, Ying (Phytotaxa, 2026)
Tirpitzia meiguensis, a species described in 2023, is the focus of this study. Based on botanical resource surveys conducted in the areas surrounding its type locality, detailed dissection and observation revealed several diagnostic characteristics: its corolla is white, occasionally tinged with pale pink (vs. uniformly white in congeners); the number of stigmas ranges from 3 to 5 (vs. 4–5); and between the fertile stamens, there is either a single linear-lanceolate staminode or a staminode with 2–3 teeth (vs. consistently 3-toothed). In addition to its type locality in Meigu County, this species has also been recorded in neighboring Zhaojue County, suggesting that its existing population size may be considerably larger than previously reported. This paper provides supplementary description of the surface papillae of the flowering branches and discussion on the reduction of seed wings in T. meiguensis, aiming to offer foundational data for a better understanding of the evolutionary systematics within the genus.